2023
DOI: 10.1079/cabireviews.2023.0001
|View full text |Cite
|
Sign up to set email alerts
|

Potential of plant growth-promoting rhizobacteria to improve crop productivity and adaptation to a changing climate

Abstract: Abiotic and biotic stresses negatively affect the growth and yield of crops worldwide. It is estimated that abiotic and biotic stresses account for global food crop losses of 50% and 30%, respectively. With the rapidly growing world population expected to reach 10 billion by 2050, the issue of food security is becoming a global concern. Climate change, which has its roots in industrialization, urbanization, and agricultural activities, further exacerbates food crop losses. Various innovative agricultural techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 135 publications
0
9
0
Order By: Relevance
“…Intriguingly, although all four strains isolated from tomato rhizospheres are favorable to potato yield, only SLU99 is significantly beneficial to tomato yield. Previous research found that bacterial consortiums aid plant growth by enhancing stress tolerance (Silambarasan et al, 2019; Yang et al, 2021; Kelbessa et al, 2023). Recently, results from our group demonstrated that SLU99 is compatible with strains EV23 and AV10 (Kelbessa et al, 2022), implying that these bacteria could co-exist as a consortium in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, although all four strains isolated from tomato rhizospheres are favorable to potato yield, only SLU99 is significantly beneficial to tomato yield. Previous research found that bacterial consortiums aid plant growth by enhancing stress tolerance (Silambarasan et al, 2019; Yang et al, 2021; Kelbessa et al, 2023). Recently, results from our group demonstrated that SLU99 is compatible with strains EV23 and AV10 (Kelbessa et al, 2022), implying that these bacteria could co-exist as a consortium in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, although all four strains are favorable to potato yield, only SLU99 is significantly beneficial to tomato yield. Previous research found that bacterial consortiums aid plant growth by enhancing stress tolerance ( Silambarasan et al., 2019 ; Yang et al., 2021 ; Kelbessa et al., 2023 ). Recently, results from our group demonstrated that SLU99 is compatible with strains EV23 and AV10 ( Kelbessa et al., 2022 ), implying that these bacteria could co-exist as a consortium in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the economic ramifications of climate-induced crop failures can hinder the purchasing power of rural communities, affecting food utilization [27]. Addressing these interconnected dimensions is vital for formulating comprehensive strategies to safeguard food security in the face of a changing climate [28].…”
Section: Food Security In Rural Areasmentioning
confidence: 99%
“…The negative impact of climate change on food security is well-documented in the literature [13], [28], [31], [32]. Agricultural systems are highly vulnerable to changing climatic conditions, which can lead to decreased crop productivity and increased food insecurity [33].…”
Section: Climate Change and Its Impactsmentioning
confidence: 99%